2018
DOI: 10.17659/01.2018.0047
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis: A Traumatic Etiology

Abstract: Background: Blunt abdominal trauma as a cause of acute appendicitis has only been rarely reported in literature. However, controversy exists as to whether the diagnosis of appendicitis in a traumatic setting is a causal or coincidental finding. Case Report: A 22 year old, previously fit and healthy male, fell from a height of 3 meters landing onto his right side onto a concrete floor. Primary and secondary survey revealed right upper quadrant tenderness on examination and soft tissue swelling of the right shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…AA following blunt abdominal trauma is not common, and in a systematic review, 28 cases with appendicitis following blunt trauma were reported between 1991-2009 (4). Moreover, several case reports discussed the same situation (9)(10)(11). However, no prospective study has investigated the relation and pathophysiology of appendicitis after blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…AA following blunt abdominal trauma is not common, and in a systematic review, 28 cases with appendicitis following blunt trauma were reported between 1991-2009 (4). Moreover, several case reports discussed the same situation (9)(10)(11). However, no prospective study has investigated the relation and pathophysiology of appendicitis after blunt trauma.…”
Section: Discussionmentioning
confidence: 99%